JavaScript - Smith, Alfred; Virtual Training Company ([Australia] : Virtual Training Company, 2008)
This course provides in-depth hands-on experience writing client-side JavaScript. VTC author, Al Smith teaches how to integrate JavaScript into web pages and walks through hands-on examples
Title from container
Training CD
Contains 94 movies with total time 6.5 hours
System requirements: Mac: System 9 or higher ; PC: Windows 98 or higher, 32MB System RAM, 6MB Video RAM, 16x CD-ROM ; QuickTime 6
Keywords: JavaScript (Computer program language); World Wide Web